Liver Transplant for Cholangiocarcinoma - Zamora-Valdes, Daniel; Heimbach, Julie K (Gastroenterology clinics of North America, 2018)
Liver transplant (LT) for perihilar cholangiocarcinoma (CCA) offers an opportunity for survival among patients with early-stage but anatomically unresectable disease. The 5-year survival rate after LT is 65% to 70%, higher among patients with primary sclerosing cholangitis, who are often diagnosed earlier, and lower among patients with de novo CCA. The results of LT for hilar CCA, along with recent limited data suggesting favorable survival among patients with very early intrahepatic CCA (ICC), have reignited interest in the subject. This article discusses LT following neoadjuvant therapy for CCA and the early data on LT alone for ICC.